Geochemical Reservoir Analysis Of The Gunung Ungaran Geothermal Prospect, Semarang District, Central Java Province - Karyanto, .; Wahyudi, .; Suharno, .; Ari, Setiawan; Wiwit, Suryanto (UGM, 2012)
The Gunung Ungaran geothermal prospect situated within the Semarang District, Central Java Province. Geochemical data collected from sixteen location. The geochemical analysis using the ions balance, geothermometer and geoindikator analysis, doe to determine the reservoir characteristic and temperature conditions of the Gunung Ungaran geothermal prospect, Semarang District, Jawa Tengah Province. The tentative result, although the ions balance indicate that not good balance, but the geoindictor and geothermometer indicated that the characteristic of the reservoir should be acid with temperature more than 200° C.